2017
DOI: 10.1007/s10450-017-9900-7
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy–entropy compensation for isosteric state adsorption at near ambient temperatures

Abstract: List of symbols AbstractThe adsorption process at near ambient temperatures indicated that the EEC (enthalpy-entropy compensation) is affected by three basic thermodynamic values: ∆H, ∆S and T. The consequence is that it is possible to determine an isosteric straight (symbol H − S) without experimental studies based on the slope coefficient T iso , which is the constant arising from the expected temperature range (about 0-60 °C). Therefore, EEC curves can be obtained by appropriate modification of the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The net isosteric heat (q st ) and differential molar entropy (∆S) exhibited a linear relation (Figure 4) with coefficient of determination of R 2 of 0.9994, implying that the compensation existed between the two quantities. This linear relationship between q st and ∆S for water sorption has been previously reported for various food products (Fasina, 2006;McMinn, Al-Muhtaseb, & Magee, 2005;Mianowski & Urbańczyk, 2017;Pushpadass et al, 2014;Sharma et al, 2009;Thanuja & Ravindra, 2014).…”
Section: Enthalpy-entropy Compensation Theorysupporting
confidence: 83%
See 3 more Smart Citations
“…The net isosteric heat (q st ) and differential molar entropy (∆S) exhibited a linear relation (Figure 4) with coefficient of determination of R 2 of 0.9994, implying that the compensation existed between the two quantities. This linear relationship between q st and ∆S for water sorption has been previously reported for various food products (Fasina, 2006;McMinn, Al-Muhtaseb, & Magee, 2005;Mianowski & Urbańczyk, 2017;Pushpadass et al, 2014;Sharma et al, 2009;Thanuja & Ravindra, 2014).…”
Section: Enthalpy-entropy Compensation Theorysupporting
confidence: 83%
“…The isokinetic temperature ( T B ) and free energy constant (∆ G ) estimated using Equation (9) by linear regression for all sets of data were obtained as 491.53 K and 1.129, respectively, whereas the value of harmonic mean temperature ( T hm ) derived from Equation (10) as 269 K. The statistical test proposed by Krug, Hunter, & Grieger, (1976), wherein if the condition of T B ≠ T hm with linear correlation between q st and ∆ S was satisfied, it was implied as a further validation of the compensation theory for the sorption process (Goula et al, 2008; Lamharrar et al., 2007; Mianowski & Urbańczyk, 2017). Furthermore, Leffler (1955) reported that, if T B > T hm , the process was enthalpy‐driven, while the sign of the value of ∆ G provided a means for prediction of spontaneity of water sorption; a negative sign was reflective of a spontaneous process and vice versa (Apostolopoulos & Gilbert, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of ∆H° gives information whether the adsorption is exothermic or endothermic. The adsorption process is exothermic if the value of ∆H° is negative and the adsorption process is endothermic if the value of ∆H° is positive (Denayer, and Baron, 2005;Miawnowski, and Urbanczyk, 2017). The value of ∆S° related to the degree of freedom of the adsorbed species.…”
Section: Pseudo-second-order Kinetic Modelmentioning
confidence: 99%